2017
DOI: 10.1080/15350770.2018.1404403
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a Win-Win Situation” – Intergenerational Learning in Preschool and Elder Care Settings: An Irish Perspective

Abstract: This paper explores the level and sustainability of intergenerational practice in early years and elder care settings in Ireland. The paper is based on a small-scale research study involving interviews with sta in ve organizations and builds on ndings from previous research conducted for the TOY project (http://www.toyproject.net). The paper examines the pedagogies involved as well as the community context of intergenerational practice in early years and elder care settings. The ndings highlight that sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…For older adults, and children often growing up without grandparents in close proximity, there are fewer opportunities for casual intergenerational engagement (Femia et al 2008). This can result in the stereotyping of older and younger people and lack of understanding across generations, compounding both social isolation and a sense of loneliness (Gallagher and Fitzpatrick 2018;Giraudeau and Bailly 2019;Hanmore-Cawley and Scharf 2018;Kuehne and Melville 2014;Macfarlane et al 2019;Sun et al 2019;Teater 2016;Yasunaga et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For older adults, and children often growing up without grandparents in close proximity, there are fewer opportunities for casual intergenerational engagement (Femia et al 2008). This can result in the stereotyping of older and younger people and lack of understanding across generations, compounding both social isolation and a sense of loneliness (Gallagher and Fitzpatrick 2018;Giraudeau and Bailly 2019;Hanmore-Cawley and Scharf 2018;Kuehne and Melville 2014;Macfarlane et al 2019;Sun et al 2019;Teater 2016;Yasunaga et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Real Life Learning model could be considered evidence of an older, more traditional approach, where care and nurture are prioritised in practice, and where learning to be, learning to learn, and learning to live together (OECD 2006) are deeply rooted values underpinning the daily routine of activities in childminding homes. In changing times, such continuity of values across generations (Gallagher and Fitzpatrick 2018) can contribute to a stable, substantial, relational foundation for young children's lives.…”
Section: Discussionmentioning
confidence: 99%
“…The link between intergenerational learning and children's transfer of knowledge, attitudes and/or climate-friendly actions to their parents is themed in several studies, and is often referred to as a multiplier, spillover or catalyst effect [24,31,43,[46][47][48]. In this case, children who participate in an environmental program and affect their parents in their decisions concerning climate change can be seen as multipliers or catalysts [26,28,32,46,49].…”
Section: Intergenerational Learning and Multiplier Effectsmentioning
confidence: 99%
“…It is already known that there are several influences on the multiplier effect; however, the various effects and their interrelationship is yet to be confirmed [25,28,29,45,49]. Nilsson et al [25] have noted that the strength of the multiplier effect is dependent on context similarity, personality, self-identity and/or framing, and it has been demonstrated that the link to intergenerational communication and the relationship between children and parents does play an important role [36,46,48,50,51]. According to this complex variety of influencing factors, it is not surprising that increasing knowledge does not necessarily change attitudes or even actions [3,34].…”
Section: Intergenerational Learning and Multiplier Effectsmentioning
confidence: 99%
See 1 more Smart Citation